Chiropractic Manipulation: Reasons for Concern? - Gouveia, LO (2007)
Chiropractic's popularity is rising among the general population. Moreover, few studies have been conducted to properly evaluate its safety. We report three cases of serious neurological adverse events in patients treated with chiropractic manipulation. The first case is a 41 years old woman who developed a vertebro-basilar stroke 48 h after cervical manipulation. The second case represents a 68 years old woman who presented a neuropraxic injury of both radial nerves after three sessions of spinal manipulation. The last case is a 34 years old man who developed a cervical epidural haematoma after a chiropractic treatment for neck pain. In all three cases there were criteria to consider a causality relation between the neurological adverse events and the chiropractic manipulation. The described serious adverse events promptly recommend the implementation of a risk alert system.